Indicators of Inclusive Business Model: perception of business and government agency communities in Taman Negara Pahang, Kuala Tahan, Pahang, Malaysia - Shuib, Ahmad; Chia, Kei Wei; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman; Abdul Karim, Hafiza; Kamaludin, Mohd Hafez (2012)
The development of rural tourism has been identified as a strategic alternative to overcome the economic decline in the rural agricultural sector. The growth of the rural tourism hinges upon the benefits accruing to the local communities in terms of employment, business opportunities, entrepreneurial development, asset accumulation, environmental conservation and improved standard of living. The establishment of the Inclusive Business Model (IBM) could expedite and ensure that benefits of rural tourism can be sustained; or this to happen, supports of the communities are critical in order to optimize the positive effects of IBM. The paper explores the perception of the members of the business community and public agencies on the indicators and criteria needed for the establishment of the IBM in the area. The case study shows that in Taman Negara Pahang, Kuala Tahan, in general, members of the business community and the staffs of various public agencies feel that there are attributes that could aid in the establishment of IBM, however, there is an immediate need for a championing entity to lead, create and apply the model in the present context.